PERANCANGAN INTERIOR PUSAT EDUWISATA PENCAK SILAT DENGAN TEMA DONGKREK DI KABUPATEN MADIUN - Pamungkas, Qohin Hadi; Indarto, Indarto (Sanggitarupa, 2022)
The interior design of the Pencak Silat Edutourism Center in Madiun Regency will become a new facility in the tourism sector as a tourist facility and a means to introduce the art of pencak silat as well as to accommodate and develop the art of pencak silat which is a potential art and culture in Madiun Regency. This design will lift the contemporary style with the theme of the jack. In realizing a comfortable and safe design for its users, the interior design of the Pencak Silat Edutourism Center will use several approaches to support the design process, including a functional approach, an ergonomics approach, an aesthetic approach, and a technical approach. The design method that will be used is the Kurtz programming method. This design will have facilities including a lobby area, martial arts gallery, raden prawirodipuro room (silat workshop), kentungan store, gong cafe and restaurant, kenong library, audio visual drum, roro ayu room (multipurpose room), office, service area, and prayer room. . The results of this design can be used as a reference and reference in interior designing, especially those with the same design object as this design.